African-Atlantic cultures and the South Carolina lowcountry - Brown, Ras Michael, 1970- (Cambridge : Cambridge University Press, 2013)
"African-Atlantic Cultures and the South Carolina Lowcountry examines perceptions of the natural world revealed by the religious ideas and practices of African-descended communities in South Carolina from the colonial period into the twentieth century. Focusing on Kongo nature spirits known as the simbi, Ras Michael Brown describes the essential role religion played in key historical processes, such as establishing new communities and incorporating American forms of Christianity into an African-based spirituality. This book illuminates how people of African descent engaged the spiritual landscape of the Lowcountry through their subsistence practices, religious experiences, and political discourse"--
Machine generated contents note: 1. Place, culture, and power; 2. Land of the living; 3. African spirits of the land and water; 4. African landscapes of the Lowcountry; 5. Spiritual guardians in the wilderness; 6. Mermaid histories and power.
Includes bibliographical references and index.
Description based on print version record.
Keywords: African Americans -- Religion; Africans -- South Carolina -- Religion; Congo (Democratic Republic) -- Religion; South Carolina -- Religion; Christianity and other religions -- Congo (Democratic Republic); South Carolina -- Social life and customs; HISTORY / World; RELIGION / Religious Intolerance, Persecution & Conflict; Electronic books